2015
DOI: 10.1182/blood-2015-01-620302
|View full text |Cite
|
Sign up to set email alerts
|

A European collaborative study of cyclophosphamide, bortezomib, and dexamethasone in upfront treatment of systemic AL amyloidosis

Abstract: Key Points CyBorD achieves excellent outcome in noncardiac patients with AL amyloidosis and can rescue subjects with reversible heart damage. The outcome of high-risk patients remains poor, but response to CyBorD can also improve survival in this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
278
2
15

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 368 publications
(302 citation statements)
references
References 23 publications
7
278
2
15
Order By: Relevance
“…Chemotherapeutic regimens containing the proteasome inhibitor bortezomib have shown efficacy and good tolerance profile in both AL amyloidosis [26][27][28] and Randall-type MIDD [25] but their effect on the clearance of LC tissular deposits, although possibly accepted, remains to be demonstrated. Interestingly, Komatsuda et al [29] reported the disappearance of nodular mesangial lesions and disappearance of kappa light chain deposits in a patient with kidney LCDD under longterm chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapeutic regimens containing the proteasome inhibitor bortezomib have shown efficacy and good tolerance profile in both AL amyloidosis [26][27][28] and Randall-type MIDD [25] but their effect on the clearance of LC tissular deposits, although possibly accepted, remains to be demonstrated. Interestingly, Komatsuda et al [29] reported the disappearance of nodular mesangial lesions and disappearance of kappa light chain deposits in a patient with kidney LCDD under longterm chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, hematologic response rates in our patients are very similar to those reported in larger collaborative series. 9 Higher doses of cyclophosphamide could probably be more effective, as in the EVOLUTION study, but at the expense of increased toxicity. 25 Recent data indicate that patients bearing plasma cell clones with certain cytogenetic abnormalities may have a less favorable outcome with bortezomib-based therapies; 26 however, cytogenetics were available only in a small number of patients, thus we cannot make statistically meaningful comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…24 Another important question concerns the dose of cyclophosphamide, which is lower than what is commonly used in myeloma patients. Such moderate doses are commonly used in most centers, [8][9][10] although some physicians prefer to use oral rather than the intravenous route, which may affect pharmacodynamics and pharmacokinetics of cyclophosphamide as this drug needs to be activated in the liver. Nonetheless, hematologic response rates in our patients are very similar to those reported in larger collaborative series.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Bortezomib is a proteasome inhibitor with activity in plasma cell disorders that has been reported to achieve high rates of hematologic and organ response in amyloidosis. 5,6 Treatment with bortezomib pre-AHCT has been shown to improve transplant eligibility for patients, previously considered to be too high risk for AHCT, and may increase the response rates following AHCT. [7][8][9][10] Herein, we describe our experience using bortezomib prior to AHCT and demonstrate the feasibility of this approach.…”
mentioning
confidence: 99%